Online research to guide knowledge management planning - Steckler, A.; Farel, A.; Bontempi, J.B.; Umble, K.; Polhamus, B.; Trester, A. (Health Education Research, 2001)
The current paper describes the process and results of an effort to find a way to effectively manage and diffuse prevention knowledge. This study shows the role that today's communication technologies can play in ensuring collaboration and participation in both the design and use of a knowledge management system (KMS) for prevention research, practice and policy. In the context of this study, 'prevention research' includes primary through tertiary prevention efforts consistent with general applied public health research in the US. An online Delphi study was used to engage a set of prevention research constituencies in the design of a mechanism to enhance the potential for effective technology transfer. A three-round Delphi was conducted with 58 stakeholders and key informants involved in prevention: government-level policy makers, researchers and front-line practitioners. The study resulted in consensus on 34 functions and 32 output/content elements of a proposed web-based KMS called Prevention-Effects.net. The paper also describes the implications of both the processes of development and the benefits of the proposed system for those interested in prevention.
Keywords: Delphi Technique; Health Services Research; Humans; Information Services; Internet; Online Systems; Planning Techniques; Preventive Health Services; Technology Transfer; United States; User-Computer Interface; adult; article; dept.pch; health care planning; health care policy; health care system; human; interpersonal communication; major clinical study; management; medical research; priority journal; scoring system

Can health professionals learn qualitative evaluation methods on the World Wide Web? A case example - Steckler, A; Farel, A; Bontempi, JB; Umble, K; Polhamus, B; Trester, A (Health Education Research, 2001)
The Enhancing Data Utilization Skills through Information Technology (EDUSIT) project trained Maternal and Child Health professionals to collect, analyze and interpret data via a year-long web-based course. The overall goal of the project was to strengthen the technology and analytic skills of the public health workforce. This article describes and analyzes a web-based module for training public health professionals to use qualitative research and evaluation methods that was one of six offered within the EDUSIT project. The qualitative module consisted of six units: overview of qualitative methods, planning qualitative studies, conducting field observations, qualitative interviewing, analyzing qualitative data and presenting qualitative findings. Evaluation results found no statistically significant changes in specific knowledge or beliefs about qualitative methods. However, the change in participants' self-efficacy was statistically significant. Participants' self-reports also showed significant changes in perceived skill levels in `collecting qualitative data through an interview' and `analyzing and interpreting qualitative data'. Most participants rated each lesson within the qualitative methods module as valuable, and most found the teaching methods used satisfactory, emphasizing the value of both the didactic teaching and the practical exercises and team project. The most common difficulty reported was finding the time to complete the module requirements while also working full-time. Implications of these findings for web-based teaching of public health professionals are discussed.
Keywords: Adult; Competency-Based Education; Data Collection; Education, Distance; Education, Graduate; Educational Measurement; Evaluation Studies; Health Knowledge, Attitudes, Practice; Health Personnel; Humans; Internet; Job Satisfaction; Middle Aged; Self Efficacy; Southeastern United States; Teaching; adult; article; data analysis; dept.pch; education; health care personnel; human; human experiment; information processing; priority journal; public health; scoring system; self report; statistical analysis; teaching